Litchi-shaped phenolic resin-based porous carbon, preparation method, negative electrode material and battery
Patent Information
- Application Number
- CN202611197371.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对以上技术问题,本发明提供了一种荔枝形酚醛树脂基多孔炭、制备方法、负极材料及电池,本发明提供的荔枝形酚醛树脂基多孔炭,依靠其多孔与荔枝形骨架结构,可有效缓冲硅充放电过程中的体积膨胀,提升锂离子传输效率,解决了现有酚醛树脂基碳材料电化学性能不佳的技术问题
[0016] Compared with existing technologies, this invention provides a litchi-shaped phenolic resin-based porous carbon, its preparation method, a negative electrode material, and a battery. First, the litchi-shaped phenolic resin-based porous carbon prepared by this invention, compared with traditional spherical, blocky, or amorphous phenolic resin-based carbon materials, has unique surface protrusions. These surface protrusions constitute a multi-level rough structure and form a litchi-like morphology. On the one hand, this improves the uniformity of silicon loading and expands the effective contact area between the overall negative electrode and the electrolyte, thereby improving lithium-ion transport efficiency and effectively enhancing the electrochemical performance of the negative electrode material. Second, the porous structure of the litchi-shaped phenolic resin-based porous carbon of this invention can effectively buffer the volume expansion during silicon charging and discharging, preventing electrode structure collapse and improving the cycle stability of the negative electrode material.
Smart Images

Figure CN122916103A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery anode material technology, specifically to a litchi-shaped phenolic resin-based porous carbon, its preparation method, anode material, and battery. Background Technology
[0002] Lithium-ion batteries, with their advantages of high energy density, excellent cycle life, and no memory effect, have been widely used in many fields such as portable electronic devices, new energy vehicles, and energy storage systems. The anode material is a key component of lithium-ion batteries, and its performance directly determines the battery's lithium storage capacity, cycle stability, and rate capability. Silicon-based anode materials possess characteristics such as ultra-high theoretical specific capacity (4200 mAh / g), abundant reserves in the Earth's crust, and environmental friendliness, making them the ideal next-generation anode material for constructing high-energy-density lithium-ion batteries.
[0003] However, pure silicon materials have significant drawbacks. During repeated lithium insertion and extraction, it undergoes dramatic volume expansion, which can easily lead to electrode structure cracking and active material peeling off. Simultaneously, silicon's poor conductivity severely impacts the cycle stability and rate performance of lithium-ion batteries, limiting its commercial application. The current mainstream solution in the industry is silicon-carbon composite modification. Leveraging the excellent conductivity and framework stability of carbon materials, it effectively buffers the volume deformation of silicon, synergistically improving the overall electrochemical performance of the electrode. Among these, phenolic resin carbon precursors offer high carbonization yield, easily controllable microstructure, and low raw material costs. The porous carbon prepared by carbonization exhibits excellent conductivity and abundant pore structure, making it an excellent carrier for loading nano-silicon to prepare composite anodes.
[0004] However, the phenolic resin-based carbon materials prepared by existing technologies still have insufficient uniformity of silicon loading and buffering effect of volume expansion, resulting in the electrochemical performance of lithium-ion batteries prepared from them failing to meet requirements. Summary of the Invention
[0005] To address the above technical problems, this invention provides a litchi-shaped phenolic resin-based porous carbon, a preparation method, a negative electrode material, and a battery. The litchi-shaped phenolic resin-based porous carbon provided by this invention, relying on its porous and litchi-shaped framework structure, can effectively buffer the volume expansion during silicon charging and discharging, improve lithium-ion transport efficiency, and solve the technical problem of poor electrochemical performance of existing phenolic resin-based carbon materials.
[0006] The specific technical solution of the present invention is as follows: According to one aspect of the present invention, a litchi-shaped phenolic resin-based porous carbon is provided, wherein the litchi-shaped phenolic resin-based porous carbon is a spherical particle, the surface of the spherical particle has a multi-level rough structure, the multi-level rough structure is composed of protrusions distributed on the particle surface, forming a litchi-shaped morphology.
[0007] In the above technical solution, the specific surface area of the litchi-shaped phenolic resin-based porous carbon is 1950~2167 m². 2 / g, pore volume 0.89~0.98cm³ 3 / g, with an average pore diameter of 1.78~2.08nm.
[0008] According to another aspect of the present invention, the present invention also provides a method for preparing the above-mentioned litchi-shaped phenolic resin-based porous carbon, comprising the following steps: S1. Phenol, formaldehyde and alkaline catalyst are mixed once, then pore-forming agent and morphology modifier are added, and the mixture is mixed a second time to obtain litchi-shaped phenolic resin. S2. After carbonizing the litchi-shaped phenolic resin, litchi-shaped phenolic resin carbonized material is obtained. S3. After the litchi-shaped phenolic resin carbon material is mixed evenly with activator and water, it is dried and activated to obtain the litchi-shaped phenolic resin-based porous carbon.
[0009] In the above technical solution, in step S1, the temperature of the first mixing is 40~60℃, and the time of the first mixing is 10~20min.
[0010] In the above technical solution, in step S1, the secondary mixing is: first, the temperature is raised to 60~80℃ and mixed for 1~2 hours, and then the temperature is raised to 80~95℃ and mixed for 2~4 hours.
[0011] In the above technical solution, in step S2, the carbonization treatment is as follows: the litchi-shaped phenolic resin is placed in an inert gas environment and subjected to three heating treatments in sequence: the first heating is to 290~310℃, the second heating is to 590~610℃, and the third heating is to 800~1000℃.
[0012] In the above technical solution, the heating rate of the first heating is 2~5℃ / min, and the holding time is 1~2h; the heating rate of the second heating is 1~3℃ / min, and the holding time is 2~3h; the heating rate of the third heating is 1~2℃ / min, and the holding time is 2~4h.
[0013] In the above technical solution, in step S3, the activation treatment is: in an inert gas environment, the temperature is raised to 700-900℃ at a heating rate of 2-5℃ / min and held for 1-3 hours.
[0014] According to another aspect of the present invention, the present invention also provides a negative electrode material, comprising the litchi-shaped phenolic resin-based porous carbon or the litchi-shaped phenolic resin-based porous carbon prepared by the preparation method described above.
[0015] According to yet another aspect of the invention, the invention also provides a battery comprising the aforementioned negative electrode material.
[0016] Compared with existing technologies, this invention provides a litchi-shaped phenolic resin-based porous carbon, its preparation method, a negative electrode material, and a battery. First, the litchi-shaped phenolic resin-based porous carbon prepared by this invention, compared with traditional spherical, blocky, or amorphous phenolic resin-based carbon materials, has unique surface protrusions. These surface protrusions constitute a multi-level rough structure and form a litchi-like morphology. On the one hand, this improves the uniformity of silicon loading and expands the effective contact area between the overall negative electrode and the electrolyte, thereby improving lithium-ion transport efficiency and effectively enhancing the electrochemical performance of the negative electrode material. Second, the porous structure of the litchi-shaped phenolic resin-based porous carbon of this invention can effectively buffer the volume expansion during silicon charging and discharging, preventing electrode structure collapse and improving the cycle stability of the negative electrode material. Attached Figure Description
[0017] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0018] Figure 1 This is a scanning electron microscope image of the litchi-shaped phenolic resin-based porous carbon of Example 1 of the present invention, magnified at 1000x. Figure 2 This is a scanning electron microscope image of the litchi-shaped phenolic resin-based porous carbon of Example 1 of the present invention, magnified at 10,000 times. Figure 3 This is a graph showing the first charge and discharge curves of the battery module in Embodiment 1 of the present invention; Figure 4 This is a differential capacity curve of the battery module in Embodiment 1 of the present invention during its first cycle. Figure 5 This is a graph showing the first charge and discharge curves of the battery module in Embodiment 2 of the present invention; Figure 6 This is a differential capacity curve of the battery module in Embodiment 2 of the present invention during the first cycle. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of this invention more apparent, the invention is described in detail below. It should be understood that the invention is not limited to the description herein.
[0020] The multi-level roughened structure of this invention comprises a hierarchical surface uneven structure composed of micron-sized large protrusions and nano-sized micro protrusions, with no restrictions on regular arrangement, forming a lychee-like morphology. As an example, micron-sized large protrusions refer to surface protrusion structures with a height of 1-3 micrometers; nano-sized micro protrusions refer to nanoscale protrusion structures attached to the surface of micron-sized protrusions, with a height of 10-200 nanometers. In this invention, the multi-level roughened structure serves to improve the uniformity of silicon loading, significantly increase the effective contact area of the porous carbon surface, provide more active sites for lithium-ion insertion and extraction, and simultaneously enhance the wetting and adhesion effect between particles and electrolyte, thereby improving electrochemical performance.
[0021] The phenol used in this invention is a core polymeric monomer raw material known in the art for use in the synthesis of phenolic resins, and this invention is not limited to industrial-grade or analytical-grade phenol of specific purities. As an example, industrially refined phenol or chemically polymerized phenol, with a purity ≥99%, can be used to meet the synthesis requirements. In this invention, the role of phenol is to undergo a condensation polymerization reaction with formaldehyde to form the core structure of the phenolic resin polymer backbone, providing a carbon source for subsequent carbonization molding.
[0022] The formaldehyde used in this invention is a cross-linking monomer known in the art for use in the condensation polymerization of phenol to prepare phenolic resins, and this invention is not limited to specific forms of formaldehyde raw materials such as aqueous formaldehyde solution or paraformaldehyde. As an example, a 37wt% aqueous formaldehyde solution can be used. In this invention, the role of formaldehyde is to undergo a condensation cross-linking reaction with phenol, promoting the cross-linking and solidification of the phenolic resin molecular chains to form a stable spherical resin precursor structure, ensuring the subsequent litchi morphology molding effect.
[0023] The alkaline catalyst used in this invention is a known additive in the art for catalyzing the condensation reaction of phenol and formaldehyde to synthesize thermosetting phenolic resins, and this invention is not limited to a single alkaline catalyst. As an example, the alkaline catalyst can be a conventional alkaline catalytic medium for phenolic resin synthesis, such as sodium hydroxide, potassium hydroxide, ammonia, or triethylamine. In this invention, the role of the alkaline catalyst is to regulate the reaction rate and extent of the condensation reaction, promote the directional polymerization of phenol and formaldehyde, avoid uneven resin polymerization and disordered morphology, and ensure the initial formation of the basic morphology of the litchi-shaped resin.
[0024] The porogen used in this invention is a functional additive known in the art for use in the preparation of polymer resin-based carbon materials and subsequent pore-forming and pore-building processes. Furthermore, this invention is not limited to a single type of porogen raw material. As an example, environmentally friendly additives that can decompose and volatilize or pyrolyze at high temperatures to create pores, such as polyethylene glycol, glucose, starch, and sodium bicarbonate, can be selected as porogens. In this invention, the role of the porogen is to decompose and volatilize during the carbonization and activation processes of the resin, reserving initial pore channels within the carbon material, and synergistically constructing a porous structure with the target specific surface area, pore volume, and pore size through the activation process.
[0025] The morphology modifier used in this invention is a specialized modifying agent known in the art for controlling the microstructure of phenolic resin polymerization, and this invention is not limited to a single morphology modifier. As an example, surfactants, polymeric dispersants, and other additives can be selected as morphology modifiers. In this invention, the role of the morphology modifier is to induce the formation of a spherical matrix and a multi-level protrusion structure on the surface during the polymerization of phenolic resin, shaping a lychee-like morphology and preventing resin particles from agglomerating and developing irregular morphologies.
[0026] The activator used in this invention is a known additive in the art for high-temperature activation and pore-forming modification of carbon materials, and this invention is not limited to a single type of activator. As an example, conventional high-temperature chemical activators for carbon materials such as potassium hydroxide, sodium hydroxide, and potassium carbonate can be selected as the activator. In this invention, the role of the activator is to undergo an etching reaction with the carbon matrix during the high-temperature activation stage, further enriching the pore structure and controlling the specific surface area, pore volume, and average pore diameter of the porous carbon to the target parameter range.
[0027] This invention provides a litchi-shaped phenolic resin-based porous carbon, which is a spherical particle with a multi-level rough structure on the surface of the particle. The multi-level rough structure is composed of protrusions distributed on the particle surface, forming a litchi-shaped morphology.
[0028] In this invention, the specific surface area of the litchi-shaped phenolic resin-based porous carbon is 1950~2167 m². 2 / g, pore volume 0.89~0.98cm³ 3 / g, with an average pore diameter of 1.78~2.08nm.
[0029] This invention also provides a method for preparing litchi-shaped phenolic resin-based porous carbon, comprising the following steps: S1. Phenol, formaldehyde and alkaline catalyst are mixed once, then pore-forming agent and morphology modifier are added, and the mixture is mixed a second time to obtain litchi-shaped phenolic resin. S2. After carbonizing the litchi-shaped phenolic resin, litchi-shaped phenolic resin carbonized material is obtained. S3. After mixing the litchi-shaped phenolic resin carbon material with activator and water evenly, and then drying and activating it, litchi-shaped phenolic resin-based porous carbon is obtained.
[0030] In step S1 of the present invention, the molar ratio of phenol to formaldehyde is 1:1.2~1.5, preferably 1:1.3~1.4.
[0031] In step S1 of this invention, the mass of the alkaline catalyst is 2% to 5% of the mass of phenol, preferably 3% to 4%; the alkaline catalyst includes one or more of sodium hydroxide, ammonia, and barium hydroxide; the amount of pore-forming agent added is 10% to 30% of the mass of phenol, preferably 15% to 25%; the pore-forming agent includes one or more of polyethylene glycol, polyvinyl alcohol, and starch; the mass of the morphology modifier is 5% to 15% of the mass of phenol, preferably 8% to 12%; the morphology modifier includes one or more of hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and Tween-80.
[0032] In step S1 of this invention, the temperature of the first mixing is 40~60℃, preferably 45~55℃; the time of the first mixing is 10~20min, preferably 12~18min.
[0033] In step S1 of this invention, the secondary mixing involves first heating to 60-80°C and mixing for 1-2 hours, preferably at 65-75°C for 1.2-1.8 hours, followed by heating to 80-95°C and mixing for 2-4 hours, preferably at 85-90°C for 2.5-3.5 hours. In step S1 of this invention, the particle size of the litchi-shaped phenolic resin is 1-10 μm.
[0034] In step S2 of this invention, the carbonization process is as follows: the litchi-shaped phenolic resin is placed in an inert gas environment and subjected to three heating treatments in sequence: the first heating is to 290~310℃, preferably 295~305℃; the second heating is to 590~610℃, preferably 595~605℃; and the third heating is to 800~1000℃, preferably 850~950℃.
[0035] In this invention, the heating rate for the first heating is 2~5℃ / min, preferably 3~4℃ / min, and the holding time is 1~2h, preferably 1.2~1.8h; the heating rate for the second heating is 1~3℃ / min, preferably 1.5~2.5℃ / min, and the holding time is 2~3h, preferably 2.2~2.8h; the heating rate for the third heating is 1~2℃ / min, preferably 1.2~1.8℃ / min, and the holding time is 2~4h, preferably 2.5~3.5h.
[0036] In step S2 of this invention, the inert gas is either nitrogen or argon; the gas flow rate of the inert gas is 100~300 mL / min, preferably 150~250 mL / min.
[0037] In step S2 of this invention, the particle size of the litchi-shaped phenolic resin carbonized material is 0.5~8μm.
[0038] In step S3 of this invention, the mass ratio of litchi-shaped phenolic resin carbonizer to activator is 1:2~4, preferably 1:2.5~3.5; the activator includes one or more of potassium hydroxide, sodium hydroxide and phosphoric acid.
[0039] In step S3 of this invention, the drying temperature is 80~100℃, preferably 85~95℃; the drying time is 12~24h, preferably 15~20h. In step S3 of this invention, the activation treatment is as follows: under an inert gas environment, the temperature is increased to 700~900℃ at a rate of 2~5℃ / min, preferably 3~4℃ / min, preferably 750~850℃, and held at that temperature for 1~3h, preferably 1.5~2.5h.
[0040] In step S3 of this invention, the inert gas is either nitrogen or argon; the gas flow rate of the inert gas is 100~300 mL / min, preferably 150~250 mL / min.
[0041] In step S3 of this invention, after the activation treatment is completed, the furnace is first cooled to room temperature, and then washed with a 1-2 mol / L hydrochloric acid aqueous solution, preferably a 1.2-1.8 mol / L hydrochloric acid aqueous solution, until neutral. Then it is washed with water 3-5 times, dried, and pulverized to obtain litchi-shaped phenolic resin-based porous carbon.
[0042] The present invention also provides a negative electrode material comprising litchi-shaped phenolic resin-based porous carbon prepared by a method thereof.
[0043] This invention also provides a method for preparing the aforementioned negative electrode material, comprising the following steps: A1. Place the litchi-shaped phenolic resin-based porous carbon into a tube CVD furnace, introduce argon gas at a gas flow rate of 200~400mL / min, preferably 250~350mL / min, and then raise the temperature to 600~650℃, preferably 610~640℃, at a heating rate of 5~10℃ / min, preferably 6~8℃ / min and hold it at that temperature for 30~60min, preferably 40~50min. A2. Adjust the gas flow rate to 100~200mL / min, preferably 120~180mL / min, introduce silicon source gas, control the furnace pressure to 200~300Pa, preferably 220~280Pa, and carry out the vapor deposition reaction for 2~4h, preferably 2.5~3.5h. Then, stop the introduction of silicon source gas, keep it at the temperature for 30~60min, preferably 40~50min, and then cool it to room temperature with the furnace to obtain a porous carbon composite material loaded with nano-silicon. A3. Introduce acetylene and argon gas in a volume ratio of 2:7~9, preferably 2:7.5~8.5, heat to 800~1000℃, preferably 850~950℃ and hold for 1~2h, preferably 1.2~1.8h, to form a carbon coating layer with a thickness of 5~10nm on the surface of the porous carbon composite material loaded with nano-silicon, and obtain the negative electrode material after cooling.
[0044] In step A2 of this invention, the volume ratio of silicon source gas to argon gas is 1:4~6, preferably 1:4.5~5.5; the silicon source gas includes one of silane and dichlorosilane.
[0045] The present invention also provides a battery comprising a negative electrode material.
[0046] The present invention also provides a method for preparing the battery as described above, comprising the following steps: B1. After mixing the negative electrode material with a conductive agent, a binder and water to obtain a negative electrode slurry, the slurry is uniformly coated on the surface of a copper foil with a coating thickness of 50~100μm, preferably 60~80μm. The slurry is dried at 80~100℃, preferably 85~95℃ for 12~24h, preferably 15~20h, and then rolled under a pressure of 10~20MPa, preferably 12~18MPa, to obtain a silicon-carbon negative electrode sheet. B2. Mix the positive electrode active material, conductive agent, binder and N-methylpyrrolidone to obtain a positive electrode slurry, then coat it evenly on the surface of aluminum foil, and after drying and rolling, obtain a positive electrode sheet. B3. The positive electrode, separator, and silicon-carbon negative electrode are stacked in sequence, placed in the battery casing, and electrolyte is injected. After encapsulation, formation, and aging, the battery is obtained.
[0047] In step B1 of this invention, the mass ratio of the negative electrode material to the conductive agent and the binder is (80~90):(5~10):(5~10), preferably (83~87):(6~8):(6~8); the conductive agent includes one or more of carbon black, graphene and carbon nanotubes; the binder is composed of sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1~3.
[0048] In step B1 of this invention, the areal density of the silicon-carbon anode sheet is 10~20 mg / cm³. 2 The compaction density of the silicon-carbon anode sheet is 1.2~1.5 g / cm³. 3 .
[0049] In step B2 of this invention, the mass ratio of the positive electrode active material, the conductive agent, and the binder is (90~95):(2~5):(2~5), preferably (92~94):(3~4):(3~4); the positive electrode active material is LiCoO2, LiFePO4, or LiNi. 1 / 3 Co 1 / 3Mn 1 / 3 One or more of O2.
[0050] In step B3 of this invention, the diaphragm is made of polypropylene, polyethylene, or a polypropylene / polyethylene composite diaphragm; the electrolyte uses LiPF6 as the solute with a concentration range of 1.0~1.2 mol / L, and the solvent is a carbonate, including one or more of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate.
[0051] In step B3 of this invention, the formation includes the following steps: charging at 25°C with a constant current of 0.05~0.1C, preferably 0.06~0.09C, to 4.2~4.3V, preferably 4.22~4.28V, followed by constant voltage charging until the current drops to 0.01C, and then letting it stand for 1~2 hours, preferably 1.2~1.8 hours; then discharging at a constant current of 0.1~0.2C, preferably 0.12~0.18C, to 2.5~3.0V, preferably 2.6~2.9V, to complete the formation.
[0052] In step B3 of this invention, aging is performed at 25°C for 24-48 hours, preferably at 25°C for 30-40 hours.
[0053] To further illustrate the present invention, detailed descriptions will be provided below through the following embodiments. The raw materials used in the following embodiments and comparative examples of the present invention are all commercially available products, including: sodium carboxymethyl cellulose (CMC2200); styrene-butadiene rubber (AL-1002); polypropylene membrane with a thickness of 20 μm; polypropylene / polyethylene composite membrane with a thickness of 20 μm; polyethylene glycol (PEG-400); polyvinyl alcohol (PVA-1788); and ammonia water with a concentration of 26 wt%. Example 1 Preparation of litchi-shaped phenolic resin-based porous carbon: Phenol and formaldehyde in a molar ratio of 1:1.3 were heated to 50°C, and 3% sodium hydroxide by weight of phenol was added. After mixing for 15 min, 25% polyethylene glycol by weight of phenol and 12% hexadecyltrimethylammonium bromide by weight of phenol were added. The mixture was first heated to 70°C and mixed for 1.5 h, and then heated to 90°C and mixed for 3 h to obtain litchi-shaped phenolic resin with a particle size of 3~8 μm. Preparation of litchi-shaped phenolic resin carbonized material: The litchi-shaped phenolic resin was placed in nitrogen gas at a flow rate of 200 mL / min and subjected to three heating treatments in sequence: first, the temperature was raised to 300℃ at a rate of 3℃ / min and held for 1.5 h; then, the temperature was raised to 600℃ at a rate of 2℃ / min and held for 2.5 h; finally, the temperature was raised to 900℃ at a rate of 1.5℃ / min and held for 3 h, to obtain litchi-shaped phenolic resin carbonized material with a particle size of 1~6 μm. Preparation of litchi-shaped phenolic resin-based porous carbon: Litchi-shaped phenolic resin carbon material and activator were mixed at a mass ratio of 1:3. Water, with a mass twice the sum of the two, was added and mixed thoroughly. The mixture was dried at 90℃ for 18 hours. Then, under a nitrogen atmosphere with a gas flow rate of 200 mL / min, the temperature was increased to 850℃ at a rate of 3℃ / min and held for 2 hours. The mixture was first cooled to room temperature in the furnace, then washed with a 1.5 mol / L hydrochloric acid aqueous solution until neutral, followed by washing four times with water. After drying and pulverizing, litchi-shaped phenolic resin-based porous carbon was obtained. The scanning electron microscope image of the litchi-shaped phenolic resin-based porous carbon is shown below. Figure 1 (Magnification is 1000x) Figure 2 (Magnification is 10000x) As shown, by Figure 1 and Figure 2 It can be seen that the phenolic resin-based porous carbon exhibits a typical litchi morphology. Preparation of the negative electrode material: Lychee-shaped phenolic resin-based porous carbon was placed in a tube CVD furnace. Argon gas was introduced at a flow rate of 300 mL / min, and the temperature was raised to 620℃ at a rate of 8℃ / min and held for 45 min. The gas flow rate was adjusted to 150 mL / min, and silane (silane to argon volume ratio of 1:5) was introduced. The furnace pressure was controlled at 250 Pa, and the vapor deposition reaction was carried out for 3 h. The silane was then stopped, and the temperature was held for 45 min. The mixture was then cooled to room temperature with the furnace to obtain a porous carbon composite material loaded with nano-silicon. Acetylene and argon gas with a volume ratio of 2:8 were introduced, and the temperature was raised to 900℃ and held for 1.5 h to form a carbon coating layer on the surface of the porous carbon composite material loaded with nano-silicon. After cooling, the negative electrode material was obtained. Battery preparation: A negative electrode material, carbon black, and binder in a mass ratio of 85:7:8 were mixed, and water was added to obtain a negative electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of copper foil to a thickness of 80 μm. After drying at 90°C for 18 h, it was rolled under a pressure of 15 MPa to obtain a silicon-carbon negative electrode sheet. A positive electrode slurry in a mass ratio of 92:4:4 was mixed, and N-methylpyrrolidone was added to obtain a positive electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of aluminum foil, dried, and rolled to obtain a positive electrode sheet. The positive electrode sheet, polypropylene separator, and silicon-carbon negative electrode sheet were then combined. The cells were stacked sequentially, placed into a battery casing, injected with electrolyte, and sealed. They were then charged at 25°C with a constant current of 0.08C to 4.2V, followed by constant voltage charging until the current dropped to 0.01C, and allowed to stand for 1.5 hours. Next, they were discharged at a constant current of 0.15C to 3.0V to complete formation. Finally, they were aged at 25°C for 36 hours to obtain the battery. The binder consisted of sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:2. The electrolyte solute was LiPF6 with a molar concentration of 1.1 mol / L. The solvent consisted of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1.
[0054] Example 2 Preparation of litchi-shaped phenolic resin-based porous carbon: Phenol and formaldehyde in a molar ratio of 1:1.4 were heated to 55°C, and 4% ammonia water (by weight of phenol) was added. After mixing for 18 min, 28% polyvinyl alcohol (by weight of phenol) and 13% sodium dodecylbenzenesulfonate (by weight of phenol) were added. The mixture was first heated to 75°C and mixed for 1.8 h, and then heated to 92°C and mixed for 3.5 h to obtain litchi-shaped phenolic resin with a particle size of 1~5 μm. Preparation of litchi-shaped phenolic resin carbonized material: The litchi-shaped phenolic resin was placed in argon gas at a flow rate of 250 mL / min and subjected to three heating treatments in sequence: first, the temperature was raised to 300℃ at a rate of 4℃ / min and held for 1.8 h; then, the temperature was raised to 600℃ at a rate of 2.5℃ / min and held for 2.8 h; finally, the temperature was raised to 950℃ at a rate of 1.8℃ / min and held for 3.5 h, to obtain litchi-shaped phenolic resin carbonized material with a particle size of 0.5~4 μm; Preparation of litchi-shaped phenolic resin-based porous carbon: Litchi-shaped phenolic resin carbon material and activator were mixed at a mass ratio of 1:3.5, and water with a mass twice the sum of the two was added and mixed evenly. After drying at 95℃ for 20h, the temperature was raised to 880℃ at a gas flow rate of 4℃ / min under an argon atmosphere with a gas flow rate of 250mL / min and held for 2.5h. The mixture was first cooled to room temperature in the furnace, then washed with 1.8mol / L hydrochloric acid aqueous solution until neutral, and then washed with water 4 times. After drying and pulverizing, litchi-shaped phenolic resin-based porous carbon was obtained. Preparation of the negative electrode material: Lychee-shaped phenolic resin-based porous carbon was placed in a tube CVD furnace. Argon gas was introduced at a flow rate of 350 mL / min, and the temperature was raised to 630℃ at a rate of 9℃ / min and held for 50 min. The gas flow rate was adjusted to 180 mL / min, and silane (silane to argon volume ratio of 1:5.5) was introduced. The furnace pressure was controlled at 280 Pa, and the vapor deposition reaction was carried out for 3.5 h. The silane was then stopped, and the temperature was held for 50 min. The mixture was then cooled to room temperature with the furnace to obtain a porous carbon composite material loaded with nano-silicon. Acetylene and argon gas with a volume ratio of 2:8.5 were introduced, and the temperature was raised to 950℃ and held for 1.8 h to form a carbon coating layer on the surface of the porous carbon composite material loaded with nano-silicon. After cooling, the negative electrode material was obtained. Battery fabrication: Anode material, graphene, and binder in a mass ratio of 88:6:6 were mixed, and water was added to obtain anode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of copper foil to a thickness of 85 μm. The slurry was dried at 95°C for 20 h, followed by rolling under a pressure of 18 MPa to obtain a silicon-carbon anode sheet. LiNi in a mass ratio of 93:3.5:3.5 was then used... 1 / 3 Co 1 / 3Mn 1 / 3O2, carbon nanotubes, and binders are mixed, and N-methylpyrrolidone is added to obtain a positive electrode slurry with a solid content of 50%. This slurry is then uniformly coated onto the surface of aluminum foil, dried, and rolled to obtain a positive electrode sheet. The positive electrode sheet, polypropylene / polyethylene composite separator, and silicon-carbon negative electrode sheet are stacked sequentially, placed in a battery casing, injected with electrolyte, and sealed. The battery is then charged at 25°C with a constant current of 0.09C to 4.25V, followed by constant voltage charging until the current drops to 0.01C, and allowed to stand for 1.8 hours. It is then discharged at a constant current of 0.18C to 2.8V to complete the formation process. Finally, the battery is aged at 25°C for 40 hours to obtain the final battery. The binder consists of sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:2.5. The electrolyte solute is LiPF6 with a molar concentration of 1.15 mol / L. The solvent consists of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:2:2.
[0055] Example 3 Preparation of litchi-shaped phenolic resin-based porous carbon: Phenol and formaldehyde in a molar ratio of 1:1.2 were heated to 40°C, and 2% of barium hydroxide by mass of phenol was added. After mixing for 20 min, 10% of polyethylene glycol by mass of phenol and 5% of Tween-80 by mass of phenol were added. The mixture was first heated to 60°C and mixed for 2 h, and then heated to 80°C and mixed for 4 h to obtain litchi-shaped phenolic resin with a particle size of 3~8 μm. Preparation of litchi-shaped phenolic resin carbonized material: The litchi-shaped phenolic resin was placed in argon gas at a flow rate of 100 mL / min and subjected to three heating treatments in sequence: first, the temperature was raised to 290℃ at a rate of 2℃ / min and held for 2 h; then, the temperature was raised to 590℃ at a rate of 1℃ / min and held for 3 h; finally, the temperature was raised to 800℃ at a rate of 1℃ / min and held for 4 h, to obtain litchi-shaped phenolic resin carbonized material with a particle size of 2~8 μm. Preparation of litchi-shaped phenolic resin-based porous carbon: litchi-shaped phenolic resin carbonized material and potassium hydroxide were mixed at a mass ratio of 1:2. Water with a mass of twice the sum of the two masses was added and mixed evenly. After drying at 80℃ for 24h, the temperature was raised to 700℃ at a gas flow rate of 100mL / min under a nitrogen atmosphere and held at 2℃ / min for 3h. The mixture was first cooled to room temperature in the furnace, then washed with 1mol / L hydrochloric acid aqueous solution until neutral, and then washed three times with water. After drying and pulverizing, litchi-shaped phenolic resin-based porous carbon was obtained. Preparation of the negative electrode material: Lychee-shaped phenolic resin-based porous carbon was placed in a tube CVD furnace. Argon gas was introduced at a flow rate of 200 mL / min, and the temperature was raised to 600℃ at a rate of 5℃ / min and held for 60 min. The gas flow rate was adjusted to 100 mL / min, and dichlorosilane (the volume ratio of dichlorosilane to argon gas was 1:4) was introduced. The furnace pressure was controlled at 200 Pa, and the vapor deposition reaction was carried out for 4 h. The silicon source gas was then stopped, and the temperature was held for 60 min. The mixture was then cooled to room temperature with the furnace to obtain a porous carbon composite material loaded with nano-silicon. Acetylene and argon gas with a volume ratio of 2:7 were introduced, and the temperature was raised to 800℃ and held for 2 h to form a carbon coating layer on the surface of the porous carbon composite material loaded with nano-silicon. After cooling, the negative electrode material was obtained. Battery preparation: A negative electrode material, carbon black, and binder were mixed in a mass ratio of 80:10:10. Water was added to mix the mixture, resulting in a negative electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of copper foil to a thickness of 50 μm. After drying at 80°C for 24 h, it was rolled under a pressure of 10 MPa to obtain a silicon-carbon negative electrode sheet. A positive electrode slurry was mixed in a mass ratio of 90:5:5 with LiFePO4, carbon black, and binder. N-methylpyrrolidone was added to mix the mixture, resulting in a positive electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of aluminum foil, dried, and rolled to obtain a positive electrode sheet. The positive electrode sheet, polypropylene separator, and... Silicon-carbon anode sheets are stacked sequentially, placed in a battery casing, electrolyte is injected, and after encapsulation, the battery is charged at 0.05C at 25°C to 4.2V under constant current, followed by constant voltage charging until the current drops to 0.01C, and then left to stand for 1 hour. The battery is then discharged at 0.1C at constant current to 2.5V to complete formation. It is then aged at 25°C for 24 hours to obtain the battery. The binder consists of sodium carboxymethyl cellulose and styrene-butadiene rubber in a 1:1 mass ratio. The electrolyte solute is LiPF6 with a molar concentration of 1.1 mol / L. The solvent consists of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a 1:1:1 volume ratio.
[0056] Example 4 Preparation of litchi-shaped phenolic resin-based porous carbon: Phenol and formaldehyde in a molar ratio of 1:1.5 were heated to 60°C, and 5% sodium hydroxide by weight of phenol was added. After mixing for 10 min, 30% polyvinyl alcohol by weight of phenol and 15% hexadecyltrimethylammonium bromide by weight of phenol were added. The mixture was first heated to 80°C and mixed for 1 h, and then heated to 95°C and mixed for 2 h to obtain litchi-shaped phenolic resin with a particle size of 4~10 μm. Preparation of litchi-shaped phenolic resin carbonized material: The litchi-shaped phenolic resin was placed in argon gas at a flow rate of 300 mL / min and subjected to three heating treatments in sequence: first, the temperature was raised to 310℃ at a rate of 5℃ / min and held for 1 h; then, the temperature was raised to 610℃ at a rate of 3℃ / min and held for 2 h; finally, the temperature was raised to 1000℃ at a rate of 2℃ / min and held for 2 h, to obtain litchi-shaped phenolic resin carbonized material with a particle size of 2~8 μm. Preparation of litchi-shaped phenolic resin-based porous carbon: litchi-shaped phenolic resin carbonized material and sodium hydroxide were mixed at a mass ratio of 1:4. Water with a mass of twice the sum of the two masses was added and mixed evenly. After drying at 100℃ for 12h, the temperature was raised to 900℃ at a gas flow rate of 300mL / min under a nitrogen / argon atmosphere and held for 1h at a heating rate of 5℃ / min. The mixture was first cooled to room temperature in the furnace, then washed with 2mol / L hydrochloric acid aqueous solution until neutral, and then washed with water 5 times. After drying and pulverizing, litchi-shaped phenolic resin-based porous carbon was obtained. Preparation of the negative electrode material: Lychee-shaped phenolic resin-based porous carbon was placed in a tube CVD furnace. Argon gas was introduced at a flow rate of 400 mL / min, and the temperature was raised to 650℃ at a rate of 10℃ / min and held for 30 min. The gas flow rate was adjusted to 200 mL / min, and dichlorosilane (the volume ratio of dichlorosilane to argon was 1:6) was introduced. The furnace pressure was controlled at 300 Pa, and the vapor deposition reaction was carried out for 4 h. The silicon source gas was then stopped, and the temperature was held for 60 min. The mixture was then cooled to room temperature with the furnace to obtain a porous carbon composite material loaded with nano-silicon. Acetylene and argon gas with a volume ratio of 2:9 were introduced, and the temperature was raised to 1000℃ and held for 1 h to form a carbon coating layer on the surface of the porous carbon composite material loaded with nano-silicon. After cooling, the negative electrode material was obtained. Battery fabrication: A negative electrode material, graphene, and binder in a mass ratio of 90:5:5 were mixed, and water was added to obtain a negative electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of copper foil to a thickness of 100 μm. After drying at 100 °C for 12 h, it was rolled under a pressure of 20 MPa to obtain a silicon-carbon negative electrode sheet. A positive electrode slurry in a mass ratio of 95:2.5:2.5 was mixed, and N-methylpyrrolidone was added to obtain a positive electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of aluminum foil, dried, and rolled to obtain a positive electrode sheet. The positive electrode sheet and polypropylene / polyethylene were then combined. The composite separator and silicon-carbon negative electrode are stacked sequentially, placed in the battery casing, injected with electrolyte, and sealed. The battery is then charged at 0.1C at 25°C to 4.3V under constant current, followed by constant voltage charging until the current drops to 0.01C, and allowed to stand for 2 hours. It is then discharged at 0.2C at constant current to 3.0V to complete formation. Finally, it is aged at 25°C for 48 hours to obtain the battery. The binder consists of sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:3. The electrolyte solute is LiPF6 with a molar concentration of 1.1 mol / L. The solvent consists of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1.
[0057] Example 5 Preparation of litchi-shaped phenolic resin-based porous carbon: Phenol and formaldehyde in a molar ratio of 1:1.2 were heated to 40°C, and 2% of barium hydroxide by mass of phenol was added. After mixing for 20 min, 10% of polyethylene glycol by mass of phenol and 5% of Tween-80 by mass of phenol were added. The mixture was heated to 80°C and mixed for 5 h to obtain litchi-shaped phenolic resin with a particle size of 1~10 μm. Preparation of litchi-shaped phenolic resin carbonized material: The litchi-shaped phenolic resin was placed in argon gas at a flow rate of 100 mL / min and subjected to three heating treatments in sequence: first, the temperature was raised to 290℃ at a rate of 2℃ / min and held for 2 h; then, the temperature was raised to 590℃ at a rate of 1℃ / min and held for 3 h; finally, the temperature was raised to 800℃ at a rate of 1℃ / min and held for 4 h, to obtain litchi-shaped phenolic resin carbonized material with a particle size of 0.5~8 μm. Preparation of litchi-shaped phenolic resin-based porous carbon: litchi-shaped phenolic resin carbonized material and potassium hydroxide were mixed at a mass ratio of 1:2. Water with a mass of twice the sum of the two masses was added and mixed evenly. After drying at 80℃ for 24h, the temperature was raised to 700℃ at a gas flow rate of 100mL / min under a nitrogen atmosphere and held at 2℃ / min for 3h. The mixture was first cooled to room temperature in the furnace, then washed with 1mol / L hydrochloric acid aqueous solution until neutral, and then washed three times with water. After drying and pulverizing, litchi-shaped phenolic resin-based porous carbon was obtained. Preparation of the negative electrode material: Lychee-shaped phenolic resin-based porous carbon was placed in a tube CVD furnace. Argon gas was introduced at a flow rate of 200 mL / min, and the temperature was raised to 600℃ at a rate of 5℃ / min and held for 60 min. The gas flow rate was adjusted to 100 mL / min, and dichlorosilane (the volume ratio of dichlorosilane to argon gas was 1:4) was introduced. The furnace pressure was controlled at 200 Pa, and the vapor deposition reaction was carried out for 4 h. The silicon source gas was then stopped, and the temperature was held for 60 min. The mixture was then cooled to room temperature with the furnace to obtain a porous carbon composite material loaded with nano-silicon. Acetylene and argon gas with a volume ratio of 2:7 were introduced, and the temperature was raised to 800℃ and held for 2 h to form a carbon coating layer on the surface of the porous carbon composite material loaded with nano-silicon. After cooling, the negative electrode material was obtained. Battery preparation: A negative electrode material, carbon black, and binder were mixed in a mass ratio of 80:10:10. Water was added to mix the mixture, resulting in a negative electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of copper foil to a thickness of 50 μm. After drying at 80°C for 24 h, it was rolled under a pressure of 10 MPa to obtain a silicon-carbon negative electrode sheet. A positive electrode slurry was mixed in a mass ratio of 90:5:5 with LiFePO4, carbon black, and binder. N-methylpyrrolidone was added to mix the mixture, resulting in a positive electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of aluminum foil, dried, and rolled to obtain a positive electrode sheet. The positive electrode sheet, polypropylene separator, and... Silicon-carbon anode sheets are stacked sequentially, placed in a battery casing, electrolyte is injected, and after encapsulation, the battery is charged at 0.05C at 25°C to 4.2V under constant current, followed by constant voltage charging until the current drops to 0.01C, and then left to stand for 1 hour. The battery is then discharged at 0.1C at constant current to 2.5V to complete formation. It is then aged at 25°C for 24 hours to obtain the battery. The binder consists of sodium carboxymethyl cellulose and styrene-butadiene rubber in a 1:1 mass ratio. The electrolyte solute is LiPF6 with a molar concentration of 1.1 mol / L. The solvent consists of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a 1:1:1 volume ratio.
[0058] Example 6 Preparation of litchi-shaped phenolic resin-based porous carbon: Phenol and formaldehyde in a molar ratio of 1:1.2 were heated to 40°C, and 2% of barium hydroxide by mass of phenol was added. After mixing for 20 min, 10% of polyethylene glycol by mass of phenol and 5% of Tween-80 by mass of phenol were added. The mixture was first heated to 60°C and mixed for 2 h, and then heated to 80°C and mixed for 4 h to obtain litchi-shaped phenolic resin with a particle size of 3~8 μm. Preparation of litchi-shaped phenolic resin carbonized material: The litchi-shaped phenolic resin was placed in argon gas at a flow rate of 100 mL / min and subjected to three heating treatments in sequence: the temperature was raised to 290℃ at a rate of 4℃ / min and held for 2 h; then the temperature was raised to 1000℃ at a rate of 1℃ / min and held for 4 h to obtain litchi-shaped phenolic resin carbonized material with a particle size of 0.5~8 μm. Preparation of litchi-shaped phenolic resin-based porous carbon: litchi-shaped phenolic resin carbonized material and potassium hydroxide were mixed at a mass ratio of 1:2. Water with a mass of twice the sum of the two masses was added and mixed evenly. After drying at 80℃ for 24h, the temperature was raised to 700℃ at a gas flow rate of 100mL / min under a nitrogen atmosphere and held at 2℃ / min for 3h. The mixture was first cooled to room temperature in the furnace, then washed with 1mol / L hydrochloric acid aqueous solution until neutral, and then washed three times with water. After drying and pulverizing, litchi-shaped phenolic resin-based porous carbon was obtained. Preparation of the negative electrode material: Lychee-shaped phenolic resin-based porous carbon was placed in a tube CVD furnace. Argon gas was introduced at a flow rate of 200 mL / min, and the temperature was raised to 600℃ at a rate of 5℃ / min and held for 60 min. The gas flow rate was adjusted to 100 mL / min, and dichlorosilane (the volume ratio of dichlorosilane to argon gas was 1:4) was introduced. The furnace pressure was controlled at 200 Pa, and the vapor deposition reaction was carried out for 4 h. The silicon source gas was then stopped, and the temperature was held for 60 min. The mixture was then cooled to room temperature with the furnace to obtain a porous carbon composite material loaded with nano-silicon. Acetylene and argon gas with a volume ratio of 2:7 were introduced, and the temperature was raised to 800℃ and held for 2 h to form a carbon coating layer on the surface of the porous carbon composite material loaded with nano-silicon. After cooling, the negative electrode material was obtained. Battery preparation: A negative electrode material, carbon black, and binder were mixed in a mass ratio of 80:10:10. Water was added to mix the mixture, resulting in a negative electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of copper foil to a thickness of 50 μm. After drying at 80°C for 24 h, it was rolled under a pressure of 10 MPa to obtain a silicon-carbon negative electrode sheet. A positive electrode slurry was mixed in a mass ratio of 90:5:5 with LiFePO4, carbon black, and binder. N-methylpyrrolidone was added to mix the mixture, resulting in a positive electrode slurry with a solid content of 50%. This slurry was then uniformly coated onto the surface of aluminum foil, dried, and rolled to obtain a positive electrode sheet. The positive electrode sheet, polypropylene separator, and... Silicon-carbon anode sheets are stacked sequentially, placed in a battery casing, electrolyte is injected, and after encapsulation, the battery is charged at 0.05C at 25°C to 4.2V under constant current, followed by constant voltage charging until the current drops to 0.01C, and then left to stand for 1 hour. The battery is then discharged at 0.1C at constant current to 2.5V to complete formation. It is then aged at 25°C for 24 hours to obtain the battery. The binder consists of sodium carboxymethyl cellulose and styrene-butadiene rubber in a 1:1 mass ratio. The electrolyte solute is LiPF6 with a molar concentration of 1.1 mol / L. The solvent consists of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a 1:1:1 volume ratio.
[0059] Performance testing The performance of litchi-shaped phenolic resin-based porous carbon, negative electrode materials, and batteries was tested according to the following test methods: Specific surface area, pore volume, and average pore diameter: A Tristar3000 fully automated specific surface area and porosity analyzer from Micron Instruments, Inc. was used to conduct nitrogen adsorption-desorption tests under liquid nitrogen cryogenic conditions. The specific surface area of the material was calculated using the BET model, and the mesopore volume and average pore diameter were determined using the BJH model. Nano-silicon loading: The absolute content of silicon in the solution was determined by completely acid digesting the sample using ICP-OES / MS. Particle size and particle size distribution: The particle size distribution and particle size of the material were tested using a Malvern MS2000 laser particle size analyzer.
[0060] 1. The specific surface area, pore volume, and average pore diameter data of the litchi-shaped phenolic resin-based porous carbon prepared in each embodiment are shown in Table 1: Table 1 Properties of Lychee-shaped Phenolic Resin-based Porous Carbon
[0061] As shown in Table 1, the litchi-shaped phenolic resin-based porous carbon prepared by this invention has a large specific surface area, pore volume, and a moderate average pore diameter.
[0062] A comparison of Examples 3 and 5 shows that when the preparation of litchi-shaped phenolic resin-based porous carbon is limited to a two-stage mixing process—first heating to 60-80°C and mixing for 1-2 hours, then heating to 80-95°C and mixing for 2-4 hours—the specific surface area and pore volume of the litchi-shaped phenolic resin-based porous carbon can be increased. A comparison of Examples 3 and 6 shows that when preparing litchi-shaped phenolic resin carbon, limiting the carbonization process to a three-stage heating process can further increase the specific surface area and pore volume of the prepared litchi-shaped phenolic resin-based porous carbon, thereby increasing the contact area between the electrolyte and the negative electrode material and improving the electrochemical performance of the battery.
[0063] 2. The properties of the negative electrode materials prepared in each embodiment are shown in Table 2: Table 2 Properties of Anode Materials
[0064] As shown in Table 2, the negative electrode materials prepared in Examples 1 and 2 of this invention have higher nano-silicon loading, more concentrated particle size distribution, and lower specific surface area, exhibiting superior performance compared to Examples 3-6. Among them, Examples 5 and 6 have lower nano-silicon loading, wider particle size distribution, and higher specific surface area. This indicates that by optimizing the preparation process and carbonization process of litchi-shaped phenolic resin-based porous carbon, this invention can further improve the nano-silicon loading and effectively control the particle size of the negative electrode material, laying the foundation for improving the electrochemical performance of the battery.
[0065] 3. Take 10 batteries prepared in Examples 1, 3-6 and connect them in series to form a battery module; place the module in the device housing, install the protection circuit, and connect the positive and negative leads; seal the housing by welding to obtain the electrochemical device, and then test its electrochemical performance. The test results are shown in Table 3 below; the first charge-discharge curve of the battery module in Example 1 is shown below. Figure 3 As shown; the differential capacity curve of the battery module in Example 1 during the first cycle is shown in the figure. Figure 4 As shown; Table 3 Electrochemical performance of batteries prepared in Examples 1, 3-6
[0066] As shown in Table 3, the battery and series module prepared by this invention exhibit excellent electrochemical performance, indicating that the litchi-shaped phenolic resin-based porous carbon prepared by this invention can effectively improve the lithium storage capacity and cycle stability of the silicon-carbon anode. Specifically, the comparison between Examples 3 and Examples 5 and 6 shows that limiting the secondary mixing process parameters during the preparation of the litchi-shaped phenolic resin-based porous carbon, and limiting the carbonization process parameters during the preparation of the litchi-shaped phenolic resin carbonization material, can further improve the electrochemical performance of the corresponding batteries.
[0067] 4. Take 12 batteries prepared in Example 2 and combine them in series and parallel (4 series and 3 parallel) to form a battery module; place the module into the device housing, install the protection circuit, and connect the positive and negative leads; seal the housing with adhesive to obtain the electrochemical device, and then test its electrochemical performance. The test results are shown in Table 4 below; the first charge and discharge curve of the battery module in Example 2 is shown below. Figure 5 As shown; the differential capacity curve of the battery module in Example 2 during the first cycle is shown in the figure. Figure 6 As shown; Table 4 Electrochemical performance of the battery prepared in Example 2
[0068] As shown in Table 4, the battery and series-parallel module prepared in Example 2 of this invention have excellent electrochemical performance, indicating that the litchi-shaped phenolic resin-based porous carbon prepared in this invention can effectively improve the lithium storage capacity and cycle stability of silicon-carbon anodes, and the prepared battery has good application prospects.
[0069] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A litchi-shaped phenolic resin-based porous carbon, characterized in that, The litchi-shaped phenolic resin-based porous carbon is a spherical particle. The surface of the spherical particle has a multi-level rough structure, which is composed of protrusions distributed on the particle surface, forming a litchi-like morphology.
2. The litchi-shaped phenolic resin-based porous carbon according to claim 1, characterized in that, The specific surface area of the litchi-shaped phenolic resin-based porous carbon is 1950~2167 m². 2 / g, pore volume 0.89~0.98cm³ 3 / g, with an average pore diameter of 1.78~2.08nm.
3. A method for preparing litchi-shaped phenolic resin-based porous carbon, used to prepare the litchi-shaped phenolic resin-based porous carbon as described in any one of claims 1-2, characterized in that, Includes the following steps: S1. Phenol, formaldehyde and alkaline catalyst are mixed once, then pore-forming agent and morphology modifier are added, and the mixture is mixed a second time to obtain litchi-shaped phenolic resin. S2. After carbonizing the litchi-shaped phenolic resin, litchi-shaped phenolic resin carbonized material is obtained. S3. After the litchi-shaped phenolic resin carbon material is mixed evenly with activator and water, it is dried and activated to obtain the litchi-shaped phenolic resin-based porous carbon.
4. The method for preparing litchi-shaped phenolic resin-based porous carbon according to claim 3, characterized in that, In step S1, the temperature of the first mixing is 40~60℃, and the time of the first mixing is 10~20min.
5. The method for preparing litchi-shaped phenolic resin-based porous carbon according to claim 3, characterized in that, In step S1, the secondary mixing is as follows: first, the temperature is raised to 60~80℃ and mixed for 1~2 hours, then the temperature is raised to 80~95℃ and mixed for 2~4 hours.
6. The method for preparing litchi-shaped phenolic resin-based porous carbon according to claim 3, characterized in that, In step S2, the carbonization process is as follows: the litchi-shaped phenolic resin is placed in an inert gas environment and subjected to three heating treatments in sequence: the first heating is to 290~310℃, the second heating is to 590~610℃, and the third heating is to 800~1000℃.
7. The method for preparing litchi-shaped phenolic resin-based porous carbon according to claim 6, characterized in that, The heating rate for the first heating is 2~5℃ / min, and the holding time is 1~2h; the heating rate for the second heating is 1~3℃ / min, and the holding time is 2~3h; the heating rate for the third heating is 1~2℃ / min, and the holding time is 2~4h.
8. The method for preparing litchi-shaped phenolic resin-based porous carbon according to claim 3, characterized in that, In step S3, the activation treatment is as follows: in an inert gas environment, the temperature is raised to 700-900℃ at a heating rate of 2-5℃ / min and held for 1-3 hours.
9. A negative electrode material, characterized in that, This includes the litchi-shaped phenolic resin-based porous carbon according to any one of claims 1 to 2, or the litchi-shaped phenolic resin-based porous carbon prepared by the preparation method according to any one of claims 3 to 8.
10. A battery, characterized in that, Includes the negative electrode material as described in claim 9.